CONTENT AND PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF TEACHERS AND EDUCATORS OF PRESCHOOL EDUCATIONAL ORGANIZATIONS - Nazirova Guzal Malikovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The study of theoretical and methodological aspects of pedagogical and psychological features of the training and advanced training of teachers-educators of preschool educational organizations and the improvement of methods of their professional development shows that there is a need to create pedagogical conditions that require high-quality organization of training in the development of professional skills and competence. Therefore, professional development of teachers-educators of preschool educational organizations is considered as a socio-pedagogical problem.